Information, Memory and Document: Study on Japanese associations in Marilia, Sao Paulo - Kajimoto, Natacha [UNESP]; Cavalcante, Lidia Eugenia; Carvalho Pazin Vitoriano, Marcia Cristina [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2017)
The first Japanese arrived in Marilia in 1926, and already in 1930, was founded the first Japanese association in this city, the Nikkei club Marilia. In 1945, another association was founded, the Sports and Cultural Association Okinawa Marilia (AECOM). These two associations brought essential contributions to the spread of Japanese culture and the construction of identity of immigrants in Marilia and region. In this context, this research aims to analyze how was the development of these associations, in relation to the information culture, memory and the Japanese identity, since they were not identified studies on this contribution to that community and to Brazilians living in Marilia. This is a qualitative research, exploratory, using as methodological procedures bibliographic and documentary research on the historical collection of the Nikkei club Marilia and Sports Association and Cultural Okinawa Marilia (AECOM), which constitute the research universe this work. Thus, we have demonstrated the importance of creating and maintaining the Japanese associations as a means of preserving the memory and transmission of knowledge among its members.
Keywords: Information; Japanese immigration and information culture; Marilia (SP, Brazil); Memory and identity; Memory Preservation